Penyuluhan Hukum Tentang Peran Guru Dalam Pencegahan Kekerasan Seksual di SMA Negeri 1 Luwuk - Lestari, Titie Yustisia; Tahir, Ridwan; Tahir, Maulana Amin; Abdullah, Abdullah; Patila, Manga; Friskanov. S, Irzha (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Sexual violence in the school environment is a problem that requires serious attention, especially from educators. This community service activity aims to increase teachers' understanding of the legal aspects in preventing sexual violence in schools. This community service activity was attended by 25 people involving teachers and students of SMA Negeri 1 Luwuk. The methods used include the presentation of interactive materials and interactive discussions. It is known that some teachers have a minimal understanding of the categories of sexual violence regulated in the law. These results demonstrate the importance of ongoing training and help teachers realize the huge role it plays in preventing sexual violence. Improving education and self-awareness is an important way to protect students from the threat of sexual violence. This means that many parties should learn about the importance of being themselves and knowing their limits when interacting with others. Teachers who have an understanding of the laws relating to sexual violence have the ability to take preventive measures, provide appropriate instruction to their students, and report incidents correctly according to legal procedures.